New insights into proteinuria/albuminuria - Comper, Wayne D.; Vuchkova, Julijana; McCarthy, Kevin J. (Frontiers in Physiology, 2022)
The fractional clearance of proteins as measured in healthy human subjects increases 10,000- 100,000- fold when studied in nephrotic patients. This remarkable increase cannot be accounted for by extracellular biophysical mechanisms centered at the glomerular filtration barrier. Rather, it is the nephron and its combination of filtration and cellular uptake that can provide a plausible explanation of these fractional clearance changes. The nephron has two regions that critically determine the level proteinuria/albuminuria. Glomerular filtration of plasma proteins is primarily a size selective event that is basically unchanged in acquired and genetic kidney disease. The glomerular concepts of ‘charge selectivity’ and of ‘large pores’, previously used to explain proteinuria, are now recognized to be flawed and non-existent. Filtered proteins then encounter downstream two protein receptors of the Park and Maack type associated with the proximal tubular cell. The high capacity receptor is thought to retrieve the majority of filtered proteins and return them to the blood supply. Inhibition/saturation of this pathway in kidney disease may create the nephrotic condition and hypoproteinemia/hypoalbuminemia. Inhibitors of this pathway (possibly podocyte derived) are still to be identified. A relatively small proportion of the filtered protein is directed towards a high affinity, low capacity receptor that guides the protein to undergo lysosomal degradation. Proteinuria in normoproteinemic states is derived by inhibition of this pathway, such as in diabetes. The combination of glomerular sieving, and the degradation and retrieval pathways can quantitatively account for the changes in fractional clearance of proteins in the nephrotic condition. Finally, the general retrieval of filtered protein by the proximal tubular cell focuses on the teleological importance of this cell as this retrieval represents the third pillar of retrieval that this cell participates in (it also retrieves water and salt).